Total soil available nitrogen under perennial grasses after burning and defoliation - Ithurrart, Leticia S. (2017)
Total soil available nitrogen concentrations (NO–3 + ) were determined underneath plants of the more-competitive Poa ligularis, mid-competitive Nassella tenuis and the less-competitive Amelichloa ambigua exposed to various combinations of controlled burning and defoliation treatments. Defoliations were at the vegetative (V), internode elongation (E) or both developmental morphology stages (V + E) during two years after burning in northeastern Patagonia, Argentina. Hypotheses were that concentrations of total soil available nitrogen after burning are greater underneath burned than unburned plants. With time, these differences, however, will gradually disappear; greater total soil available nitrogen concentrations are underneath plants of the more- than less-competitive perennial grasses; and total soil available nitrogen is similar or lower underneath plants defoliated at the various developmental morphology stages in all three study species than on untreated controls at the end of the study. Concentration of total soil available nitrogen increased 35% (p < 0.05) on average after the first six months from burning in comparison to control plants. However, these differences disappeared (p > 0.05) towards the end of the first study year. Total soil available nitrogen concentrations were at least 10% lower underneath the less competitive N. tenuis and A. ambigua than the more competitive P. ligularis on average for all treatments, although differences were not significant (p > 0.05) most of the times. Defoliation had practically no effect on the concentration of total soil available nitrogen. Rather than any treatment effect, total soil nitrogen concentrations were determined by their temporal dynamics in the control and after the experimental fire treatments.